Urinary matrix metalloproteinases-2/9 in healthy infants and haemangioma patients prior to and during propranolol therapy - Kleber, Christine; Spieß, Anne; Kleber, Jean-Baptist; Hinz, Ulf; Holland-Cunz, Stefan; Weiß, Johanna (European journal of pediatrics, 2012)
The mechanism of therapeutic success of propranolol for severe infantile haemangioma remains unclear. Propranolol was shown to modify matrix metalloproteinase (MMP) levels, which are associated with tumour pathogenesis. We hypothesized that urinary MMP2/9 is higher in patients with infantile haemangioma compared to healthy infants and that propranolol reduces MMP2/9 levels and thus leads to an involution of the haemangioma. In this case, MMP2/9 could be used as a marker of indicated therapy or therapeutic success. Urinary samples were taken before, 2 weeks after, and 2 months after the beginning of propranolol treatment in haemangioma patients and once in healthy controls. Activity of MMP2/9 was determined by commercially available activity kits. Urine of 22 haemangioma patients and 21 control subjects was obtained. Propranolol therapy had significant success in all patients. MMP2/9 was present in most samples, the younger the children the higher the MMP2 levels. Haemangioma patients showed lower levels of MMP2. The MMP2 levels were significantly higher after 2 weeks of propranolol than prior to therapy. There were no differences in MMP9 levels. Conclusions: Presence of MMP2/9 in the urine of infants <1 year can be explained by high rate of physiological tissue remodelling. Unexpectedly, MMP2 was lower in the urine of haemangioma patients and higher 2 weeks after propranolol treatment. Taking this and the diverse results in literature into account, the correlation between MMPs, proliferation, and regression of haemangiomas and propranolol remains unclear.